Chondroblastoma: An evaluation of the recurrences and functional outcomes following treatment - Devrim Özer; Yavuz Arıkan; Volkan Gür; Cantay Gök; Yunus Emre Akman (Acta Orthopaedica et Traumatologica Turcica, 2018)
Objective: Chondroblastoma is a benign aggressive tumor which needs surgical treatment and has a recurrence rate up to 35%. Extended (aggressive) curettage is the mainstay of treatment and local adjuvants have been reported to decrease the recurrence rate. Methods: The recurrence rates and the functional results of 14 patients who were treated in our institution and 2 other patients who were treated elsewhere between the years 2004–2016 were evaluated. Seventeen cases (13 male, 3 female; mean age: 17.1 [range: 13 to 32] years) who had been diagnosed, treated and followed up in our hospital between 2004 and 2016 were evaluated in terms of recurrence rates and functional outcomes. The average follow-up period was 41.6 (range: 12 to 132) months. Results: Five cases of recurrence were observed. Two cases had undergone their primary treatment in another institution. Seven cases were performed curettage alone whereas nine others were administered adjuvant treatments. One of the five recurrence patients was advised to undergo disarticulation. Another was treated with curettage and grafting and the remaining three patients with curettage and cementing. No recurrence was observed in their follow-up period. Their mean MSTS score was 27.3 (range: 4 to 30) over a maximum of 30 points and their functional results were good. Conclusion: Chondroblastoma is a tumor with high recurrence rates in the post-treatment period. However, good functional outcomes can be achieved with early diagnosis and appropriate treatment even after recurrence.Level of evidence: Level IV, therapeutic study. Keywords: Bone, Chondroblastoma, Recurrence, Treatment, Tumor